A numerical study on slip flow in packed hyper-porous media inside micro-channels using differential transformation method - Saffari, Puyan; Fatahian, Esmaeel; Saffari, Peyman; Fatahian, Hossein (International Journal of Scientific World, 2016)
Velocity slip boundary condition in parallel-plate micro-channels filled with hyper-porous media is studied using differential transformation method (DTM) in order to find an analytical approximate solution. The results focus on slip flow regime (i.e., for Knudsen numbers in the range 10−3 < Kn < 10−1). The Darcy-Brinkman-Forchheimer model is applied to study the effect of nonlinear drag term further boundary-friction effects on hydrodynamic of gas flow in micro-channels. The results show that DTM results are in good agreement with numerical ones. Also, it is observed that decreasing the value of Darcy number flattens the velocity profile while this trend is opposite for decreasing the Forchheimer number. Also, increasing the value of causes to increase the velocity slip at the wall.